Assessment of hot-melt coating methods for multiparticulate substrates: mortar-coating vs. pan-coating - Ignjatović, Jelisaveta; Đuriš, Jelena; Đuriš, Mihal; Bočarski, Teodora; Vasilijević, Vanja; Aleksić, Ivana; Cvijić, Sandra (Archives of Pharmacy, 2021)
Hot-melt coating (HMC) is an alternative, solvent-free coating method generally used to modify substrate release rate and/or mask its unpleasant taste. The aim of this study was to assess two HMC methods (pan-coating and mortar-coating) by assaying functional properties of the coated material. The selected substrates included highly soluble sodium chloride (model substance) and caffeine (bitter drug), and the coating agent was glycerol distearate without/with the addition of liquid paraffin. Experiments with sodium chloride revealed that pan-coating yielded particles of more regular shape, while mortar-coating yielded samples of more uniform coating layer. The flowability of the coated material depended on the particle size. Sustained sodium chloride release was achieved for all mortar-coated and some pan-coated samples. The analysis of the results indicated mortar-coating as a preferable HMC method for caffeine coating. The resulting caffeine yield in the coated samples was high (99%), the material showed satisfactory mechanical properties and drug release from the coated particles was sustained. Overall, the obtained results suggest that both pan- and mortar-coating can be used to sustain the release of drugs with unpleasant taste, but mortar-coating can be considered as a more simple and practical method that can be potentially used in compounding pharmacies.